2010
DOI: 10.1007/s00420-010-0580-9
|View full text |Cite
|
Sign up to set email alerts
|

An engineering intervention resulting in improvement in lung function and change in urinary 8-hydroxydeoxyguanosine among foundry workers in Taiwan

Abstract: These findings indicate that reductions in workplace respirable dust and SiO₂ concentration can result in improved lung function amongst foundry workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most of the interventions were complex and required careful consideration in design and testing. However, the studies by Gottesfeld et al ( 2019 ) and Lin et al ( 2011 ) demonstrated that simple engineering solutions such as using commercially available nozzles, general ventilation, and awareness training could significantly reduce RCS levels. Numerical simulations and laboratory experiments were carried out in the included studies to aid in designing and testing complex interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the interventions were complex and required careful consideration in design and testing. However, the studies by Gottesfeld et al ( 2019 ) and Lin et al ( 2011 ) demonstrated that simple engineering solutions such as using commercially available nozzles, general ventilation, and awareness training could significantly reduce RCS levels. Numerical simulations and laboratory experiments were carried out in the included studies to aid in designing and testing complex interventions.…”
Section: Discussionmentioning
confidence: 99%
“…These authors have expressed their inability to appraise the impact of these kinds of pollution on the human health due to the non-availability of the appropriate data. Lin et al (2011) have reported a research conducted in a foundry plant located in Taiwan. During their research, these authors have studied the impact of crystalline silica contained in the molding sand on the health of the workers.…”
Section: Foundries and Cleaner Production-a World Scenariomentioning
confidence: 98%
“…Some of the parts that are damaged due to the foundry emission are lungs, liver, kidney and brain. Lin et al (2011) have reported that the hazards caused due to the foundry workers of Taiwan. According to these authors, the silica contained in the molding sand was found to cause respiratory diseases among the foundry workers.…”
Section: Health Hazards Due To Foundry Pollutionmentioning
confidence: 98%